2021
DOI: 10.3329/bjz.v49i2.56262
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Suitable Spat Collectiors and Culture Sites for Edible Oyster in the Coast of Bay of Bengal, Bangladesh

Abstract: Potential spat collectors and suitable culture sites were investigated for the development of edible oyster culture from June to December 2019 at three study sites (Moheshkhali, the Jeti of Nuniarchora, and Sonadia) of Cox’s Bazar coast of Bangladesh. Four types of collectors such as oyster shell, earthen pot, kortal (windowpane oyster shell) and tiles were investigated. On site sampling of water quality parameters and number of spats on each collector were done at 15-days interval following standard methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…For successful reproduction and growth, oyster community must maintain a pH of less than 9 (Mathew, 2008). The average pH of the experimental area was 7.63; whereas Asaduzzaman et al (2021) showed the highest pH value was 7.92 for green mussel culture in the Moheskhali channel and Hasan et al (2021) recorded 7.68 for oyster culture in the same area. Hence, Minhaz et al (2020) stated the pH range in between 6.4-8.2 during oyster farming in Cox's Bazar coast.…”
Section: Survivalmentioning
confidence: 82%
See 4 more Smart Citations
“…For successful reproduction and growth, oyster community must maintain a pH of less than 9 (Mathew, 2008). The average pH of the experimental area was 7.63; whereas Asaduzzaman et al (2021) showed the highest pH value was 7.92 for green mussel culture in the Moheskhali channel and Hasan et al (2021) recorded 7.68 for oyster culture in the same area. Hence, Minhaz et al (2020) stated the pH range in between 6.4-8.2 during oyster farming in Cox's Bazar coast.…”
Section: Survivalmentioning
confidence: 82%
“…Temperature is one of the important factors for oyster and mussel culture. The filtering dynamism of the oyster depends on water temperature (Hasan et al, 2021;Ward et al, 2000). The rate of water transport, feeding, respiration, gonad formation and spawning possession affects by the temperature effect (Naik and Gowda, 2013).…”
Section: Survivalmentioning
confidence: 99%
See 3 more Smart Citations